Research trends and frontiers in exercise for movement disorders: A bibliometric analysis of global research from 2010 to 2021 - Chen, Ji-Wei; Guan, Yue; Zheng, Yi-Li; Zhu, Kun (Frontiers in Aging Neuroscience, 2022)
Objective: To conduct a bibliometric analysis of trends and frontiers on exercise-based nonpharmacological treatments for movement disorders published between 2010 and 2021. Methods: The Web of Science (WOS) core database was searched for papers pub-lished between 2010 and 2021. The CiteSpace software was used for in-depth analysis of the countries, institutions, journals, and collaboration networks among authors and their types of papers, developmental directions, references, and hot keywords of pub-lished papers. Results: A total of 2626 published papers were retrieved by search formula and in-cluded in the analysis. The number of publications fluctuated during this period, with 96 countries, 3058 institutions, and 886 academic journals having published papers in this area, with subject classifications that focused on Clinical Neurology and Neurosciences. The United States has maintained its dominant and most influential position in exer-cise-based non-pharmacological research on movement disorders. Among research in-stitutions and journals, the League of European Research Universities and Movement Disorders journals published the highest number of academic papers. In the last five years, the hot research topics by burst keyword analysis, are focused on treatments, re-search advances, and clinical treatments. Conclusion: Research on exercise-based non-pharmacological treatments for move-ment disorders is generally on the rise from 2010 to 2021. The bibliometric analysis of this area will help provide potential collaborations among researchers, frontiers, and di-rections for development.